CENTRAL HEMODYNAMICS IN PATIENTS WITH CARDIORENAL SYNDROME IN DIABETIC NEPHROPATHY (Modern American Journal of Medical and Health Sciences, 2025)
This article presents data on the prevalence of various types of heart remodeling in patients with type 2 diabetes with DN. It was found that the severity of structural and functional changes in the heart depends on the stage of diabetic nephropathy. New data are presented that establish a clear relationship between the indicators characterizing the structural and functional state of the heart and kidneys in patients with type 2 diabetes with DN. New facts have been obtained indicating that the basis of combined renocardial disorders in patients with type 2 diabetes is impaired vascular endothelial function.